γ‐secretase inhibitor induces adipogenesis of adipose‐derived stem cells by regulation of Notch and PPAR‐γ - Huang, Y. (Cell Prolif, 2010)
Objective:  To determine the inhibitory effect and mechanism of Notch signalling on adipogenesis of mouse adipose‐derived stem cells (mASCs). Materials and methods:  Varied concentrations of N‐[N‐(3,5‐difluorophenacetyl)‐l‐alanyl]‐S‐phenylglycine t‐butylester (DAPT) were added to mASCs 3 days before adipogenic induction with insulin‐containing differentiation medium. The process of adipogenesis and ability of lipid droplet accumulation were analysed using oil red‐O staining. The Notch signalling pathway (Notch‐1, ‐2, ‐3, ‐4, Hes‐1 and Hey‐1) and adipogenesis‐related factors (PPAR‐γ, DLK‐1/Pref‐1 and Acrp) were tested using real‐time PCR, Western blot analysis and immunofluorescence staining assays. Results:  We demonstrated that Notch‐2‐Hes‐1 signalling pathway was inhibited dose‐dependently by DAPT in mASCs. In addition, transcription of PPAR‐γ was promoted by DAPT before adipogenic induction, while inhibitor of adipogenesis DLK‐1/Pref‐1 was further depressed. At early stages of differentiation (2–4 days), adipogenesis in mASCs was advanced and significantly enhanced in 5 and 10 μm DAPT pre‐treated cases. On day 4, in differentiated mASCs cases with DAPT pre‐treatment, we also found promotion of activation of de‐PPAR‐γ and depression of HES‐1, DLK‐1/Pref‐1 mRNA and protein expression. Conclusions:  We conclude that blocking Notch signalling with DAPT enhances adipogenesis of differentiated mASCs at an early stage. It may be due to depression of DLK‐1/Pref‐1 and promotion of de‐PPAR‐γ activation, which work through inhibition of Notch‐2‐Hes‐1 pathway by DAPT.